2012
DOI: 10.1097/01.asw.0000416006.55218.d0
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Impaired Wound Healing

Abstract: This is the first installment of 2 articles that discuss the biology and pathophysiology of wound healing, review the role that growth factors play in this process, and describe current ways of growth factor delivery into the wound bed. Part 1 discusses the latest advances in clinicians’ understanding of the control points that regulate wound healing. Importantly, biological similarities and differences between acute and chronic wounds are considered, including the signaling pathways that initiate cellular and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
289
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 593 publications
(297 citation statements)
references
References 81 publications
2
289
0
6
Order By: Relevance
“…The inflammatory response following tissue injury plays important roles both in normal and pathological healing processes 19 . It provides protection against invading pathogens and remove damaged tissues 20 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…The inflammatory response following tissue injury plays important roles both in normal and pathological healing processes 19 . It provides protection against invading pathogens and remove damaged tissues 20 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…In recent decades, clini cians have gained a better understanding of the mechanisms of normal wound repair process and causes of delays in healing. 2 However, some cutaneous wounds involves complex inflammatory processes, which can lead to a more aggressive state and take longer time resulting in chronic state of inflammation. 3 Diabetic wounds are complex wounds appear as cuta neous complications arise from uncontrolled diabetes mellitus caused by hyperglycemia, oxidative stress and /or microbial infections.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies revealed that pulegone is a selective COX-2 inhibitor (24). Although no mechanism of action has been investigated, probably pulegone acts through the inhibition of the production of inflammatory mediators from the cascade of cyclooxygenase.…”
Section: Discussionmentioning
confidence: 99%